Music therapy and child development in Autism Spectrum Disorder: A systematic review (Research, Society and Development, 2026)
Objective: To synthesize findings from the literature on the effects of musicalization and music therapy on the development of children with autism spectrum disorder (ASD). Methods: A systematic review was conducted with searches in the databases and virtual library MEDLINE/PubMed, LILACS, SciELO, and the Brazilian Digital Library of Theses and Dissertations (BDTD), including studies published between 2000 and 2023 in Portuguese and English, using the terms “autism”, “autism spectrum disorder”, “autismo”, “development”, “music therapy”, “music”, “musicalization”, “musicoterapia”, “terapia musical”, “PRISMA”, and “meta-analysis”. After applying inclusion and exclusion criteria, 329 records were identified (PubMed=96, LILACS=10, SciELO=204, and BDTD=19), 41 studies remained after the initial screening stage, and 26 studies were included in the final review. Results: The included studies indicated benefits of musical interventions across multiple domains, particularly in social and affective development, verbal and nonverbal communication, motor skills, attention, creativity, and emotional and cognitive aspects. Improvements were also reported in bonding, reduction of stereotypies, increased cooperation, joint attention, imitation, and functional autonomy. However, the results were not uniform; part of the literature highlights methodological limitations, small sample sizes, heterogeneity of interventions, and insufficient follow-up time, with some studies showing no clear superiority of music therapy when associated with standard treatment. Conclusion: Musicalization shows potential as a complementary therapeutic strategy for children with ASD, especially in the domains of socialization, communication, and emotional regulation. However, the consolidation of this evidence depends on studies with more detailed and standardized methodologies to better define its clinical applicability.